An Evaluation of Mean Platelet Volume and Serum Lipid Profile in Patients with Fibromyalgia Syndrome - Ayşe İYİYAPICI ÜNÜBOL,; Gülnur TAŞCI BOZBAŞ,; Mustafa ÜNÜBOL,; Gülcan GÜRER4, (Archives of Rheumatology, 2013)
Objectives: This study aims to evaluate the mean platelet volume (MPV) and serum lipid profile in patients with fibromyalgia syndrome (FMS). Patients and methods: This retrospective study was comprised of 156 patients with FMS and 118 healthy controls who were admitted to three centers between January 2011 and December 2011. The patients' fasting blood glucose, total cholesterol, low-density lipoprotein (LDL) and high-density lipoprotein (HDL) cholesterol, triglyceride levels and complete blood count, and MPV values were recorded. The Mann-Whitney U test and Student's t-test were used according to the distribution of the data for statistical analysis. Results: The experimental power of the study was found to be 100% (0.00063), when the effect size was taken as 0.6. The MPV value was 8.75±1.15 fL in the patient group and 8.13±0.73 in the healthy controls (p<0.001). The serum triglyceride levels were significantly increased in the patients with FMS compared with the healthy controls (p=0.003). Conclusion: We found that the MPV, one of the early markers of atherosclerosis, was significantly high in the FMS patients.